Psychosocial support for mothers experiencing psychological stress in early childhood interventions: a mixed-methods evaluation in Austria - Tonja Ofner; Sophie Sagerschnig; Fiona Scolik; Philipp Schöch; Jean Lillian Paul (Archives of Public Health, 2026)
Abstract Background Psychological stress during pregnancy and early motherhood is a major public health concern with significant implications for maternal wellbeing and early child development. Persistent stress during this period can adversely affect maternal mental health, parent–child interactions, and the developmental trajectories of infants. Early childhood intervention programs aim to provide preventive support to vulnerable families; however, systematic evaluations of psychosocial services embedded within these programs remain limited. Understanding how such services meet maternal needs and contribute to health outcomes is essential for informing service delivery and policy. This study evaluates two psychosocial services offered to mothers experiencing psychological stress in Tyrol and Vienna as part of the Austrian Early Childhood Intervention Program “Frühe Hilfen”. The study aimed to explore the needs of mothers participating in early childhood interventions and to assess the perceived benefits and challenges of two psychosocial services from the perspectives of both mothers and healthcare providers. Methods A summative evaluation using a mixed-methods design was conducted. Data were collected through focus groups and individual interviews with participating mothers and healthcare providers, complemented by standardized screening instruments to assess maternal mental health and wellbeing. Qualitative data were analyzed using content analysis to identify recurring themes, perceptions, and experiences, while quantitative screening data were analyzed descriptively to examine changes in maternal outcomes. Results Participating mothers valued the services for their low-threshold access, professional support, and flexibility. In Tyrol, mothers reported improvements in mental health and self-efficacy following participation in short-term psychotherapeutic interventions. In Vienna, group therapy sessions facilitated peer support, reduced feelings of isolation, and strengthened parenting confidence. The group setting enabled mothers to share experiences, build trust, and develop supportive networks. Improvements were also reflected in screening scores. At the same time, barriers such as language limitations and limited service capacity were identified. Conclusions Psychosocial services embedded within early childhood interventions can make an important contribution to perinatal and infant mental healthcare. The findings highlight the value of accessible psychosocial support for mothers experiencing psychological stress while identifying structural barriers that should be addressed to improve access and service capacity within the public health systems.